Statistics in a civil war: The case of the Tigray health system. Issue 4 (27th July 2022) - Gebregziabher, Mulugeta; Cochran, James J.
Abstract : Ukraine is not the only country whose health‐care system has been ravaged by conflict. Here, Mulugeta Gebregziabher and James J. Cochran describe the huge challenges of gathering reliable data on the catastrophic effect of civil war in Tigray, Ethiopia Abstract : Ukraine is not the only country whose health‐care system has been ravaged by conflict. Mulugeta Gebregziabher and James J. Cochran describe the huge challenges of gathering reliable data on the catastrophic effect of civil war in Tigray, Ethiopia